A randomised controlled trial of flow driver and bubble continuous positive airway pressure in preterm infants in a resource-limited setting. Issue 1 (13th August 2015) - Mazmanyan, P; Mellor, K; Doré, C J; Modi, N
Abstract : Objectives: The variable-flow flow driver (FD; EME) and continuous-flow bubble (Fisher-Paykel) continuous positive airway pressure (CPAP) systems are widely used. As these differ in cost and technical requirements, determining comparative efficacy is important particularly where resources are limited. Design: We performed a randomised, controlled, equivalence trial of CPAP systems. We specified the margin of equivalence as 2 days. We analysed binary variables by logistical regression adjusted for gestation, and log transformed continuous variables by multiple linear regression adjusted for gestation, sex and antenatal steroids. Setting: A neonatal unit with no blood gas analyser or surfactant availability and limited X-ray and laboratory facilities Patients: Neonates <37 weeks of gestation. Interventions: We provided CPAP at delivery followed by randomisation to FD or bubble (B). Outcomes: Primary outcome included total days receiving CPAP; secondary outcomes included days receiving CPAP, supplemental oxygen, ventilation, death, pneumothorax and nasal excoriation. Results: We randomised 125 infants (B 66, FD 59). Differences in infant outcomes on B and FD were not statistically significant. The median (range) for CPAP days for survivors was B 0.8 (0.04 to 17.5), FD 0.5 (0.04 to 5.3). B:FD (95% CI) ratios were CPAP days 1.3 (0.9 to 2.1), CPAP plus supplementary oxygen days 1.2 (0.7 to 1.9). B:FD (95% CI) ORs were death 2.3 (0.2 to 28), ventilation 2.1 (0.5 to 9), nasal excoriation 1.2 (0.2 to 8) and pneumothorax 2.4 (0.2 to 26). Conclusions: In a resource-limited setting we found B CPAP equivalent to FD CPAP in the total number of days receiving CPAP within a margin of 2 days. Trial registration number: ISRCTN22578364.